Momentary Assessment of Psychosocial Stressors, Context, and Asthma Symptoms in Hispanic Adolescents. (January 2016) - Dunton, Genevieve; Dzubur, Eldin; Li, Marilyn; Huh, Jimi; Intille, Stephen; McConnell, Rob
The current study used a novel real-time data capture strategy, ecological momentary assessment (EMA), to examine whether within-day variability in stress and context leads to exacerbations in asthma symptomatology in the everyday lives of ethnic minority adolescents. Low-income Hispanic adolescents ( N = 20; 7th-12th grade; 54% male) with chronic asthma completed 7 days of EMA on smartphones, with an average of five assessments per day during non-school time. EMA surveys queried about where (e.g., home, outdoors) and with whom (e.g., alone, with friends) participants were at the time of the prompt. EMA surveys also assessed over the past few hours whether participants had experienced specific stressors (e.g., being teased, arguing with anyone), asthma symptoms (e.g., wheezing, coughing), or used an asthma inhaler. Multilevel models tested the independent relations of specific stressors and context to subsequent asthma symptoms adjusting for age, gender, and chronological day in the study. Being outdoors, experiencing disagreements with parents, teasing, and arguing were associated with more severe self-reported asthma symptoms in the next few hours ( p s < .05). Being alone and having too much to do were unrelated to the experience of subsequent self-reported asthma symptoms. Using a novel real-time data capture strategy, results provide preliminary evidence that being outdoors and experiencing social stressors may induce asthma symptoms in low-income Hispanic children and adolescents with chronic asthma. The results of this preliminary study can serve as a basis for larger epidemiological and intervention studies.